Analyzing the Role and Impact of College Students' Ideological and Political Education: Insights from the 'Three Complete Education' Framework and Its Implications for Sports Psychology - Jingyi Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The core principles of the "Three Complete Education" framework—comprehensiveness, operational integration, and theoretical alignment—provide a strong theoretical basis for constructing effective ideological and political education systems in universities. As a long-term task, ideological education must be reinforced through structured and effective educational practices. The "Three Complete Education" approach offers a holistic model of moral education, aligning with the principles of moral development and addressing the evolving needs of educational advancement. However, its implementation faces challenges such as formalism, incomplete team structures, breaks in the training process, and limited comprehensiveness in training objectives. This study examines the pathways and mechanisms for enhancing the "Three Complete Education" approach to address these challenges in the context of ideological education for college students. The effectiveness of this framework is critical to the holistic growth of students and the moral and social development of the nation. In the context of building a harmonious society, college ideological education plays a pivotal role as a component of spiritual civilization construction. The success of this education directly influences the moral character of individuals and the societal development trajectory. From the perspective of ideological and political education in colleges and universities, this article integrates theoretical insights with practical observations to propose innovative mechanisms for implementing "Three Complete Education." These innovations hold significant implications for sports psychology, particularly in fostering psychological resilience, ethical decision-making, and teamwork among students, contributing to their holistic development as morally and socially responsible individuals.